Teacher Profesionalism in Facilitating Students to Have 21st Century Skills - Yolandaru Septiana; Ani Widayati; Eka Ary Wibawa; Arif Rahman Hakim (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
This study aims to determine the readiness of vocational school teachers in facilitating students to master 21st century skills. This qualitative research using in-depth interview techniques. The respondents of this study were vocational school teachers in the Special Region of Yogyakarta. This study using thematic analysis with ATLAS.ti program. The results of the study explain that teachers' perceptions of 21st century skills vary widely, including the 4Cs (communication, creativity, collaboration, and critical thinking), technology, problem-solving skills, competence, innovation, competitive ability, religious character, and morals. Activities that have been carried out by teachers to facilitate students in mastering 21st century skills are applying various learning models, learning methods, and interesting learning media. The strategy to facilitate students to have 21st century skills is that teachers need to improve the various skills needed to teach students, namely mastery of technology. The support provided by the school is the provision of learning facilities and opportunities to participate in various scientific activities to improve their skills and professionalism. The challenges faced by teachers are the lack of understanding and use of technology and the varied backgrounds of students. Suggestions for teachers are to increase professional competence in facilitating 21st century skills.